High Prevalence of Antibodies against the Bacterium Treponema pallidum in Senegalese Guinea Baboons (Papio papio). - Sascha Knauf; Ulrike Barnett; Peter Maciej; Matthias Klapproth; Ibrahima Ndao; Sieghard Frischmann; Julia Fischer; Dietmar Zinner; Hsi Liu (PLoS ONE, 2015)
The bacterium Treponema pallidum is known to cause syphilis (ssp. pallidum), yaws (ssp. pertenue), and endemic syphilis (ssp. endemicum) in humans. Nonhuman primates have also been reported to be infected with the bacterium with equally versatile clinical manifestations, from severe skin ulcerations to asymptomatic. At present all simian strains are closely related to human yaws-causing strains, an important consideration for yaws eradication. We tested clinically healthy Guinea baboons (Papio papio) at Parc National Niokolo Koba in south eastern Senegal for the presence of anti-T. pallidum antibodies. Since T. pallidum infection in this species was identified 50 years ago, and there has been no attempt to treat non-human primates for infection, it was hypothesized that a large number of West African baboons are still infected with simian strains of the yaws-bacterium. All animals were without clinical signs of treponematoses, but 18 of 20 (90%) baboons tested positive for antibodies against T. pallidum based on treponemal tests. Yet, Guinea baboons seem to develop no clinical symptoms, though it must be assumed that infection is chronic or comparable to the latent stage in human yaws infection. The non-active character is supported by the low anti-T. pallidum serum titers in Guinea baboons (median = 1:2,560) versus serum titers that are found in genital-ulcerated olive baboons with active infection in Tanzania (range of medians among the groups of initial, moderate, and severe infected animals = 1:15,360 to 1:2.097e+7). Our findings provide evidence for simian infection with T. pallidum in wild Senegalese baboons. Potentially, Guinea baboons in West Africa serve as a natural reservoir for human infection, as the West African simian strain has been shown to cause sustainable yaws infection when inoculated into humans. The present study pinpoints an area where further research is needed to support the currently on-going second WHO led yaws eradication campaign with its goal to eradicate yaws by 2020.